SEJARAH SOSIAL ARAB-ISLAM PADA ABAD VIII DAN IX M (Studi tentang Pranata Sosial Era Abbasiah) - Daud, Al Husaini M. (Analisis: Jurnal Studi Keislaman, 2011)
The   history   of  Islamization   in  the  archipelago,   especially   that happened since the 16th century has encouraged  a writing tradition of religious manuscripts in huge numbers. The manuscripts can definitely be regarded as primary sources for reconstruction a social- intellectual  history of Indonesian  Islam in the past. One of the most important topics discussed in such sources is that relates to the history of blaming and marginalization  of religious doctrine, especially that of Unity of Being (wahdat al-wujūd), or popularly known in Java as Manunggaling  Kawula Gusti. This article will examine some Islamic works covering  the discourse  of controversy  between  the orthodoxy and heterodoxy that emerged since the mid of 16th and 19th centuries in the Archipelago. The first work that will be consulted is a Sufi treatise entitled at-Tuhfah al-Mursalah ila an-Nabi (the Gift addressed to the spirit  of the Prophet)  written  by an Indian  scholar,  Fadl Alla>>>h al- Hindi al-Burhanpuri.  Furthermore,  this article will demonstrate  the emergence  of ‘derivative’ local works  of at-Tuhfah,  written  both in Arabic  and local languages.  The works contain  both opposing  and supporting thoughts of the theosophical doctrine discussed in the at- Tuhfah.